Postcranial anatomy of Bonitasaura salgadoi (Sauropoda, Titanosauria) from the Late Cretaceous of Patagonia - Gallina, Pablo Ariel (2015)
Bonitasaura salgadoi, from the Bajo de la Carpa Formation (Santonian), Río Negro, Argentina, is a well-preserved titanosaur. Previously described cranial material of Bonitasaura demonstrated the presence of square jaws in titanosaurs, but the nearly complete postcranium of the holotype specimen remains mostly undescribed. We present an osteological description of this material, which includes cervical, dorsal, and caudal vertebrae, elements of the pectoral and pelvic girdles, as well as forelimbs and hind limbs. Characteristics of the axial skeleton suggest that the holotype represents an immature individual. The base of the neck was likely robust, based on the broad, rhomboidal neural spines in the vertebrae across the cervicodorsal transition. Bonitasaura is assigned to Titanosauria based on lateral constriction of the neural canal in the anterior cervical vertebrae, presence of anterior and posterior spinodiapophyseal laminae in the middle to posterior dorsal vertebrae, distolateral expansions of the middle dorsal vertebral neural spines, absence of hyposphene-hypantrum articulations in posterior dorsal vertebrae, anterior and middle caudal vertebrae with strongly procoelous centra, anterior caudal vertebrae with transverse processes extending beyond the posterior margin of the centrum, and other axial features. The appendicular anatomy of Bonitasaura also supports referral to Titanosauria based on characters such as the semilunar sternal plates, flat and rugose distal surfaces of the metacarpals, medial curvature of the proximal femur, posterior shallow fossa of the astagalus undivided, and mediolaterally expanded distal tibia. The gracile long bones further support placement within non-saltasaurine titanosaurs. Bonitasaura provides additional osteological data that will contribute to a better resolution of titanosaur phylogeny.